Immunological characteristics of a recombinant alphaherpesvirus with an envelope-embedded Cap protein of circovirus - Lu, Chenhe; Li, Haimin; Chen, Wenjing; Li, Hui; Ma, Jiayu; Peng, Peng; Yan, Yan; Dong, Weiren; Jin, Yulan; Pan, Shiyue; Shang, Shaobin; Gu, Jinyan; et al. (Frontiers in Immunology, 2024)
Introduction: Variant pseudorabies virus (PRV) is a newly emerged zoonotic pathogen that can cause human blindness. PRV can take advantage of its large genome and multiple non-essential genes to construct recombinant attenuated vaccines carrying foreign genes. However, a major problem is that the foreign genes in recombinant PRV are only integrated into the genome for independent expression, rather than assembled on the surface of virion. Methods: We reported a recombinant PRV with deleted gE/TK genes and an inserted porcine circovirus virus 2 (PCV2) Cap gene into the extracellular domain of the PRV gE gene using Cre-loxP recombinant system combined with CRISPR-Cas9 gene editing system. This recombinant PRV (PRV-Cap), with the envelope-embedded Cap protein, exhibits a similar replication ability to its parental virus. Results: Immunogenicity assay revealed that PRV-Cap immunized mice have 100% resistance to the lethal PRV and PCV2 attacks. Neutralization antibody and ELISPOT detections indicated that PRV-Cap can enhance neutralizing antibodies to PRV and produce IFN-γ secreting T cells specific for both PRV and PCV2. Immunological mechanistic investigation revealed that initial immunization with PRV-Cap stimulates significantly early activation and expansion of CD69+ T cells, promoting the activation of CD4 Tfh cell dependent germinal B cells and producing effectively specific effector memory T and B cells. Booster immunization with PRV-Cap recalled the activation of PRV-specific IFN-γ+IL-2+CD4+ T cells and IFN-γ+TNF-α+CD8+ T cells, as well as PCV2-specific IFN-γ+TNF-α+CD8+ T cells. Conclusion: Collectively, our data suggested an immunological mechanism that the recombinant PRV with envelope-assembled PCV2 Cap protein can serve as an excellent vaccine candidate for combined immunity against PRV and PCV2, and provided a cost-effective method for the production of PRV- PCV2 vaccine. Keywords: Chimeric pseudorabies virus; Circovirus; immunity; memory responses; IFN-γ